ANALISA KEKUATAN STRUKTUR WALKING BEAM PADA SUCKER ROD PUMP MENGGUNAKAN METODE SIMULASI NUMERIK FINITE ELEMENT ANALYSIS - Nanda; Supardi, Nurul Iman; Mainil, Afdhal Kurniawan; Winata, Alben Sindhu (UNIB Press, 2025)
Sucker rod pump are a technology that has been used for a long time in the petroleum mining industry and proven effective in lifting oil from wells that have low flow rates. One of the companies in Indonesia which still produces Sucker Rod Pump is PT. Bukaka Engineering Utama Tbk. Sucker Rod Pump is a tool that used to raise petroleum from the well to the ground surface. In a Sucker Rod Pump there are several main components, namely the Walking Beam, Horse Head, Samson Post, Crank, Counter Weight, Pitman, Equalizer, Gear Box, electric motor and V-Belt. Walking Beam is a very component has a big influence on the performance of the Pumping Unit, in this case Walking The beam on the Pumping Unit must be appropriate in terms of strength, durability and... security, this is intended to obtain effective, maximum performance. On During the design process, the Walking Beam was designed using software solidworks 2024. The material used is ASTM A36 Steel Plate, with dimensions 5000mm long, 617mm high and 200mm wide. This Walking Beam analyzed using Solidworks 2024 Software. In the Von Misses stress test, it is obtained The maximum stress result is 76,756 MPa. While the minimum voltage found on the base plate is 0.222 Mpa. For the results of the simulation The maximum displacement value obtained is 2,550 mm for color red and a minimum displacement of 41.498 mm which is indicated by blue. Lastly, safety factor testing was carried out where the results were obtained The maximum safety factor is 1,126.43 on the base plate. Meanwhile numbers The minimum security is in the blue section, namely 0.003. From the results analysis obtained, it can be seen that the Walking Beam was used it's not safe. In the analysis process the author only uses value obtained from calculating the lifting force, object mass, well volume, and the weight of the load used (ignoring the weight of the Equlizer, Pitman, Crank, and power from the gear reducer). This is done to find out what are the conditions when the Walking Beam is operating to lift fluid from At the bottom of the well then there was a problem with the drive motor.